Influence of Systematic Coupling Stiffness Parameter on Coupling Duffing System Lag Self-synchronization Characteristic - Ren, Zhao-Hui; Xu, Yu-Hang; Han, Yan-Long; Zhang, Nan; Wen, Bang-Chun (Journal of Applied Nonlinear Dynamics, 2026)
Self-synchronization, compound synchronization and intelligent control synchronization widely exist in the mechanical system engineering, while lag self-synchronization movement is a special form of cooperation movement. Based on coupling Duffing system, this paper studies lag self-synchronization problem, analyses general change law of the system co-rotating synchronization frequency, antisynchronization frequency and lag phase angle by analytic analysis and numerical quantitative analysis, studies coupling parameter influences on systematic lag self-synchronization, and analyses the cause of lag self-synchronization. The results show that the root cause of lag self-synchronization is systematic stiffness namely systematic natural characteristic; that co-rotating synchronization vibration frequency and phase difference depend on coupling stiffness parameter; and that frequency and phase difference of anti-synchronization vibration are independent of coupling stiffness parameter; and when coupling stiffness parameter is larger, phase difference of two oscillators in the two kinds of synchronization is nonzero constant value.